How is test-related information communicated in Australian Emergency Departments? – ED clinicians' and patients' perspectives. Issue 8 (August 2021) - Dahm, Maria R.; Li, Julie; Thomas, Judith; Smith, Peter; Georgiou, Andrew
Highlights: ED clinicians communicate test-related information along a continuum. Contextual factors impact the communication of test related information to patients. Patients may be unsure about accessing test-results but welcome electronic access. Health/digital literacy, skills and knowledge are perceived barriers to electronic access. Contextual factors need to be addressed to optimise test-related communication in ED. Abstract: Objectives: To investigate the communication processes involving test-related information in Australian Emergency Departments (EDs); specifically what and how ED clinicians communicate test-related information to patients, what patients know and understand about the provided information, and how patients view the potential to access their test-results electronically. Methods: We conducted face-to-face semi-structured interviews with clinicians (n = 26) and patients (n = 32) across three Australian EDs. Interviews were transcribed and analysed iteratively, following principles of qualitative content analysis and grounded theory. Results: Depending on various contextual (e.g. time pressures) and patient factors (e.g. perceived health literacy), ED clinicians provided, and patients recalled receiving, test-related information along a continuum, ranging from "no or limited" information to "specific" information. Many patients were confused about how to access their test-results. Patients welcomed the potential for future electronic access to results but viewed their individual health and/or computer literacy skills and knowledge as potential barriers. Conclusions: EDs are highly dynamic environments where contextual forces impinge on the amount and quality of test-related information that clinicians communicate to ED patients. Practice Implications: Systemic and patient factors need to be addressed to optimise the provision of test-related information in ED settings, improve patient understanding and foster patient empowerment.